2003
DOI: 10.1046/j.1460-9592.2003.01090.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind randomized placebo‐controlled trial of the effect of ketamine on postoperative morphine consumption in children following appendicectomy

Abstract: In this paediatric population intravenous ketamine did not have a morphine sparing effect. The increased incidence of side-effects, especially hallucinations, reported by patients given a ketamine infusion may limit the further use of postoperative ketamine in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
4
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 15 publications
3
41
4
1
Order By: Relevance
“…Although ketamine effects have been widely debated in adults, paediatric data are confidential and controversial [14][15][16][17]20,21]. Our findings are consistent with those of some other studies in children [14][15]17].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Although ketamine effects have been widely debated in adults, paediatric data are confidential and controversial [14][15][16][17]20,21]. Our findings are consistent with those of some other studies in children [14][15]17].…”
Section: Discussionsupporting
confidence: 89%
“…Pain scores and analgesic consumption were reduced in only two studies [17,20]. Moreover, psychomimetic effects such as hallucinations were more important in the ketamine group [14]. In a recent study, an intravenous bolus (0.2 mg kg À1 ) followed by an intraoperative infusion (5 mg kg À1 min À1 ) of S-ketamine during major urological surgery improved pain scores only during the first postoperative hour and delayed the first morphine request [16].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies in children are controversial. Some authors do not confirm the preemptive effect of ketamine on the preoperative analgesic consumption during the first hours of postoperative period in children (7,15,16). Our study showed that intravenous and subcutaneous administration of low dose ketamine reduced not only the post-operative pain score, but also analgesic requirement after tonsillectomy.…”
Section: Discussioncontrasting
confidence: 76%